Fatty acid methyl esters yield and phorbol esters degradation during transesterification of Jatropha curcas oil by alkaline, acid and enzyme catalyzed method - Tosa Koji; Ishizuka Tomoki (Renewable Energy and Environmental Sustainability, 2017)
Jatropha curcas has recently been the focus of intense research as a raw material of biomass fuel. However, the carcinogenesis promoter action of the phorbol esters in the Jatropha raises concerns for health and environmental risk. The purpose of the present study is to determine the relationship between the fatty acid methyl esters yield and the phorbol esters degradation ratio during the transesterification of the Jatropha oil by alkaline, acid and enzyme catalyzed method, respectively. The phorbol esters in Jatropha oil were degraded during the transesterification of the Jatropha curcas oil by alkaline and acid catalyzed methanol methods. The degradation ratio was significantly correlated with the fatty acid methyl esters yields in alkaline catalyzed transesterification. The results obtained in this study suggest that the health and environmental risk of the phorbol esters in a Jatropha BDF can be significantly reduced by a complete transesterification of the crude oil by controlling the transesterification condition appropriately.